Current sheets in comet 67P/Churyumov‐Gerasimenko's coma. Issue 3 (22nd March 2017) - Volwerk, M.; Jones, G. H.; Broiles, T.; Burch, J.; Carr, C.; Coates, A. J.; Cupido, E.; Delva, M.; Edberg, N. J. T.; Eriksson, A.; Goetz, C.; Goldstein, R.; et al.
Abstract : The Rosetta Plasma Consortium (RPC) data are used to investigate the presence of current sheets in the coma of comet 67P/Churyumov‐Gerasimenko. The interaction of the interplanetary magnetic field (IMF) transported by the solar wind toward the outgassing comet consists amongst others of mass loading and field line draping near the nucleus. The draped field lines lead to so‐called nested draping because of the constantly changing direction of the IMF. It is shown that the draping pattern is strongly variable over the period of one month. Nested draping results in neighbouring regions with oppositely directed magnetic fields, which are separated by current sheets. Selected events on 5 and 6 June 2015 are studied, which show that there are strong rotations of the magnetic field with associated current sheets that have strengths from several tens up to hundreds of nA/m 2 . Not all discussed current sheets show the characteristic peak in plasma density at the centre of the sheet, which might be related to the presence of a guide field. There is no evidence for different kinds of plasmas on either side of a current sheet, and no strongly accelerated ions have been observed which could have been an indication of magnetic reconnection in the current sheets. Plain Language Summary: The solar wind, consisting of plasma and magnetic field, cannot uninhabited flow past an active comet. The interaction of the gas coming out of the comet, which gets ionized, and the solar wind leads to a slowing down of the latter, and the magnetic field gets draped around the nucleus of the comet. As the solar wind magnetic field is not constant over time, there will be layers of different directions draped on top of each other, which leads to the generation of current sheets. In this paper the strength of the currents is determined, and signatures of possible magnetic reconnection are looked for but were not found. Key Points: Magnetic field line draping pattern is highly variable over time Nested draping during relatively quiet solar wind times show current sheets with strengths up to hundreds of nA/m 2 The data show no evidence that the current sheets are boundaries between different plasma regions